2014
DOI: 10.1097/ppo.0000000000000047
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Microbiome and Lymphoma Development

Abstract: The intestinal microbiota and gut immune system must communicate to maintain a balance between tolerance and activation. Our immune system protects us from pathogenic microbes at the same time that our bodies are host to trillions of microbes, symbionts, mutualists, and some that are essential to human health. Since there is such a close interaction between the immune system and the intestinal microbiota, it is not surprising that some lymphomas such as mucosal-associated lymphoid tissue (MALT) lymphoma have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 70 publications
(72 reference statements)
1
36
0
Order By: Relevance
“…Various risk factors including genetic and molecular alterations,3, 4, 5 diet,3, 6, 7 and chronic inflammation8, 9, 10 have been linked to the development of both disorders. Still other studies have suggested an association between chronic mucosal inflammation and the progression of IBD to pronounced dysplasia in the GI tract 11, 12, 13, 14…”
Section: Introductionmentioning
confidence: 98%
“…Various risk factors including genetic and molecular alterations,3, 4, 5 diet,3, 6, 7 and chronic inflammation8, 9, 10 have been linked to the development of both disorders. Still other studies have suggested an association between chronic mucosal inflammation and the progression of IBD to pronounced dysplasia in the GI tract 11, 12, 13, 14…”
Section: Introductionmentioning
confidence: 98%
“…44, 46, 47, 48, 49 Furthermore, S. bovis has also been associated with hematopoietic malignancy. 37, 50 It should be emphasized that despite the fact that oral cavity cancer, specifically squamous cell carcinoma, has been linked to numerous potential bacteria (examples include: Veillonella, Fusobacterium, Prevotella, Porphyromonas, Actinomyces, Clostridium, Haemophilus, Enterobacteriaceae, Streptococcus spp., and Gemella spp. ), no pathognomonic bacteria have yet been identified.…”
Section: Microbiome In Cancermentioning
confidence: 99%
“…Alterations in MAMPs trigger pattern receptors of innate immunity, including Toll-like receptors (TLR) and/or nucleotide-binding-oligomerization-domain (NOD)-like receptors. 37, 54 Stimulating the receptors activates the NF-κB pathway and causes expression of cytokines and interleukins.…”
Section: Microbiome In Cancermentioning
confidence: 99%
“…Since there is such a close interaction between these two players, it is not surprising that cancers of the immune system, e.g., lymphomas such as mucosal-associated lymphoid tissue (MALT) lymphomas have been shown to be caused by bacteria. These lymphomas originate in the marginal zone and 90% of MALT lymphomas are associated with the presence of Helicobacter ; elimination of Helicobacter leads to complete remission in approximately 80% of all cases(64). The causative effect of Helicobacter in MALT lymphomas has been demonstrated in animal models.…”
Section: Cancermentioning
confidence: 99%